Emerging frontiers in epigenetic-targeted therapeutics for pediatric neuroblastoma - Wang, Xiaokang; Xu, Gengrui; Ma, Hongyan; Deng, Xiaoyan; Ma, Guiping (Frontiers in Immunology, 2025)
Neuroblastoma (NB), the most prevalent extracranial solid malignancy in children, poses significant therapeutic challenges, particularly concerning high-risk subtypes characterized by an immunologically “cold” phenotype. These tumors evade immune surveillance through mechanisms such as impaired antigen presentation and immunosuppressive microenvironment formation. Despite the incorporation of immunotherapies (e.g., GD2 monoclonal antibodies) into international clinical guidelines, the 5-year survival rate of patients with NB persistently remains lower than 50%. Small-molecule targeted agents, distinguished by their low molecular weight and superior chemical stability, offer advantages over macromolecular antibody therapies by effectively penetrating cell membranes to engage intracellular targets. Epigenetic regulation, a DNA sequence-independent gene expression modulation system, plays a pivotal role in cell fate determination via dynamic DNA methylation, histone covalent modifications, chromatin spatial reorganization, and non-coding RNA-mediated pathways. Emerging evidence has highlighted a strong correlation between epigenetic dysregulation and NB progression, establishing a molecular rationale for novel therapeutic strategies. Current epigenetic research in NB primarily focuses on histone deacetylase inhibitors and DNA methyltransferase inhibitors. These drugs exhibit unique translational potential because of their accelerated development timelines and cost-effective production, significantly enhancing therapeutic accessibility. This review systematically examines the current landscape of epigenetic modulators in NB treatment and discusses their transformative potential in improving outcomes for high-risk patients with NB.